Canopy and understory nitrogen addition have different effects on fine root dynamics in a temperate forest: implications for soil carbon storage. Issue 4 (12th June 2021) - Li, Xiaowei; Zhang, Chenlu; Zhang, Beibei; Wu, Di; Shi, Yifei; Zhang, Wei; Ye, Qing; Yan, Junhua; Fu, Juemin; Fang, Chengliang; Ha, Denglong; Fu, Shenglei
Summary: Elucidating the effects of atmospheric nitrogen (N) deposition on fine root dynamics and the potential underlying mechanisms is required to understand the changes in belowground and aboveground carbon storage. However, research on these effects in forests has mostly involved direct understory addition of N and has ignored canopy interception and processing of N. Here, we conducted a field experiment comparing the effects of canopy addition of N (CAN) with those of understory addition of N (UAN) at three N‐addition rates (0, 25 and 50 kg N ha –1  yr –1 ) on fine root dynamics in a temperate deciduous forest. Fine root production and biomass were significantly higher with CAN than with UAN. At the same N‐addition rate, increases in fine root production with CAN were at least two‐fold greater than with UAN. At the high N‐addition rate and relative to the control, fine root biomass was significantly increased by CAN (by 23.5%) but was significantly decreased by UAN (by 12.2%). Our results indicate that traditional UAN may underestimate the responses of fine root dynamics to atmospheric N deposition in forest ecosystems. Canopy N processes should be considered for more realistic assessments of the effects of atmospheric N deposition in forests.